2018
DOI: 10.1111/itor.12567
|View full text |Cite
|
Sign up to set email alerts
|

A conditional directional distance function approach for measuring tax collection efficiency: evidence from Spanish regional offices

Abstract: This paper analyzes the evolution of the technical efficiency of Spanish regional tax offices with respect to the main devolved taxes for the period 2005-2014. We apply the conditional directional distance function methodology, which allows us to incorporate undesirable outputs into the production function, represented by administrative complaints lodged by taxpayers as an (inverse) measure of the quality of service provision, and account for the influence of the socioeconomic context in which these offices op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In this line, Cordero et al. (2018) argued that the main problem of the unconditional efficiency model is that it relies on an assumption that may be unrealistic. Indeed, in this model, it is implicitly assumed that all DMUs are operating under similar conditions.…”
Section: Conceptual Considerationsmentioning
confidence: 99%
“…In this line, Cordero et al. (2018) argued that the main problem of the unconditional efficiency model is that it relies on an assumption that may be unrealistic. Indeed, in this model, it is implicitly assumed that all DMUs are operating under similar conditions.…”
Section: Conceptual Considerationsmentioning
confidence: 99%
“…Second, our findings prioritize Value Revenue Collected as the main group of drivers for the overall performance of TAs. Usual 'suspects' investigated in other studies are digitalization and the use of novel technologies (Faúndez-Ugalde et al 2020;Martínez et al 2022) and human resources and culture of taxation (Chuenjit 2014;Radonić and Milosavljević 2019). Contrary to the findings of previous studies, we identified the variables in the operational excellence group (on-time filling and e-filling) as indicators that will drive excellence in the years to come.…”
Section: Contributionsmentioning
confidence: 99%
“…Fourth, we also emphasize that the CIDI methodology used in this research is data-driven rather than biased. Although some authors would prefer that a weighting scheme of composite indicators should reflect the intuitive and biased importance of the individual sub-indicators, our research is predominantly guided by the methods that advocate data-driven results, such as Data Envelopment Analysis (DEA) (Charnes et al 1978;Milanović et al 2022) or Distance Based Analysis (DBA) (Dobrota et al 2015a). Additionally, through the CIDI methodology, we provide a transparent composite indicator that is easily interpretable and comprehensive.…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, the continuous process of increasing tax burden registered in the last decades constrains tax collection by government (Mariano, 2005). Base erosion, which constitutes a serious risk to tax revenues, and recession affect the inefficiency of tax collection and constitute a serious barrier for local development process (Cordero, Dí az-Caro, Pedraja-Chaparro & Tzeremes, 2018). In this scenario, decreasing of public investments and competition for savings are inevitable (Schwengber & Ribeiro, 2000).…”
Section: Introductionmentioning
confidence: 99%